Building research capacity for sickle cell disease in Africa: Lessons and challenges from establishing a birth cohort in Tanzania - Nkya, Siana; Njiro, Belinda J.; Ngowi, Doreen; Solomon, David; Kaywanger, Frida; Nyangasa, Salama; Ndoje, Godfrey; Marco, Emmanuela; Moses, Mazoea; Makani, Julie (Frontiers in Pediatrics, 2022)
Sickle Cell Disease (SCD) is a known public health burden in sub-Saharan Africa (SSA). The manifestation of SCD starts in early childhood and if not well-managed may lead to early death (before the age of 5 years). Understanding the underlying mechanisms that influence early SCD manifestation is of great importance for early disease and intervention management which will in turn, reduce both morbidity and mortality rates in children. One approach of achieving this is by establishing SCD birth cohorts that can be followed for a period of time (3–5 years) whilst documenting necessary information related to early childhood illnesses. To date, there are few SCD birth cohorts in Africa. To address this gap, we have established a birth cohort of babies with and without SCD (with sickle cell trait and healthy babies). These babies are followed up for 3 years with their study visits synchronized to the immunization schedule. During enrollment and follow-up visits, information on demographic, clinical, and laboratory parameters are collected. To date, we have enrolled a total of 341 babies with and without SCD. Out of these, a total of 311, 186, 133, 81, 44, and 16 babies have returned for their 1st, 2nd, 3rd, 4th, 5th, and 6th visits, respectively. We have collected both demographic and clinical information for these babies at enrollment and during follow-up. We have also utilized this platform to learn on the best approaches of establishing and maintaining a research birth cohort in an African context. We have analyzed the practical issues pertaining to the integration of the birth cohort with the immunization platform which seems to be the most effective and sustainable strategy for maintaining a birth cohort in our context.